2019
DOI: 10.1002/jcp.29172
|View full text |Cite
|
Sign up to set email alerts
|

MTSS1 hypermethylation is associated with prostate cancer progression

Abstract: This study was conducted to evaluate the influence of DNA methylation of metastasis suppressor 1 (MTSS1) on prostate cancer (PCa) progression. Fortynine paired PCa tissue samples and normal tissue samples from The Cancer Genome Atlas were analyzed. Methylome analysis, CpG island arrays and Hierarchical clustering were used to analyze methylation profiles of PCa tissues. MTSS1 methylation level was detected by methylation-specific PCR. Relative messenger RNA and the expression level of MTSS1 protein were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our results also shed light on chromosome 8q24 genes that, despite their amplification, are profoundly repressed in PCa, such as MTSS1. This observation is in line with the documented epigenetic repression of this gene through different molecular means [72,73].…”
Section: Discussionsupporting
confidence: 89%
“…Our results also shed light on chromosome 8q24 genes that, despite their amplification, are profoundly repressed in PCa, such as MTSS1. This observation is in line with the documented epigenetic repression of this gene through different molecular means [72,73].…”
Section: Discussionsupporting
confidence: 89%
“…5-Aza (an HMA) has been used as a standard of care in patients with higher-risk myelodysplastic syndromes, and in those with acute myeloid leukemia ineligible for intensive therapy [36]. Meanwhile, abnormal hypermethylation has been found to impact the expression of individual genes, and was associated with the malignant progression of solid cancer [37][38][39]. However, the use of HMAs in patients with cancer has never achieved a satisfactory and beneficial overall outcome, particularly with regard to the genetic and epigenetic complexity, as well as heterogeneity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc analysis of data from a Phase 3 trial showed that the detection of serum free methylated GSTP1 (mGSTP1) DNA can predict the outcome of chemotherapy in metastatic prostate cancer and may guide treatment decisions in the clinic [26]. In addition, methylation of other genes, including olfactory 4 (OLFM4) [27], MTSS1 [7] and myeloid ecotropic viral insertion site 2 prognosis has yet to be examined in a large prostate cancer dataset. In this study, we tried to explore a classi cation method that integrates several DNA methylation markers to help clinicians evaluate the therapeutic effect and prognosis of prostate cancer patients and choose treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…These genes encompass many cellular functions, including cell cycle control, apoptosis, hormone response, DNA repair and damage prevention, signal transduction, tumor invasion and tumor suppression [5]. Frequent promoter methylation of genes such as glutathione S-transferase π (GSTP1) [6] metastasis suppressor 1 (MTSS1) [7] dedicator of cytokinesis 2 (DOCK2) [8] adenomatous polyposis coli (APC) [9] and retinoic acid receptor beta2(RARβ2) [10] has been found and is associated with the progression of prostate cancer. However, whether the methylation of these genes is related to important clinical factors, such as the degree of tumor malignancy and biochemical recurrence and prognosis, has not been determined from large datasets of patients with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%